Building digital identities: ontology development for avatars in the metaverse - Santos, Adriana Carla Ribeiro dos (2025)
Objective: To develop a comprehensive and interoperable ontology for representing avatars in the metaverse, effectively integrating the diversity of digital identities, respecting privacy and security issues, and promoting interoperability between different platforms, with the aim of providing a more cohesive, inclusive and enriching user experience. Method: Exploratory, bibliographical and descriptive application, covering authors from the fields of Information Science and Computer Science. It was developed in two phases: first, it consisted of a preparatory study to obtain the necessary knowledge about ontologies and avatars in the metaverse (consultations of books, documents and articles available in the Information Science Database, the Portal of Periodicals of the Coordination for the Improvement of Higher Education Personnel and Google Scholar); second, methodological construction of the ontology. Results: With the help of the Prot & eacute;g & eacute; ontology editor, a preliminary knowledge ontology was presented, with emphasis on its inherent flexibility and capacity for continuous evolution. Its design allows it to be easily adapted, expanded and improved to meet the specific demands of new projects, guaranteeing a dynamic structure that can adjust to different contexts and emerging needs. Conclusions: We stress that imposing a standardized model of avatars in the metaverse can have negative consequences, such as reducing diversity and perpetuating harmful stereotypes. In light of this, we suggest that platforms explore alternative ontologies that promote authenticity, inclusion and freedom of expression, with the aim of building a virtual environment that is truly diverse and representative of different identities.